The learning benefits of teaching: A retrieval practice hypothesis - Koh, Aloysius Wei Lun; Lee, Sze Chi; Lim, Stephen Wee Hun (Applied cognitive psychology, 2018)
Summary Teaching educational materials to others enhances the teacher's own learning of those to‐be‐taught materials, although the underlying mechanisms remain largely unknown. Here, we show that the learning‐by‐teaching benefit is possibly a retrieval benefit. Learners (a) solved arithmetic problems (i.e., they neither taught nor retrieved; control group), (b) taught without relying on teaching notes (i.e., they had to retrieve the materials while teaching; teaching group), (c) taught with teaching notes (i.e., they did not retrieve the materials while teaching; teaching without retrieval practice [TnRP] group), or (d) retrieved (i.e., they did not teach but only practised retrieving; retrieval practice group). In a final comprehension test 1 week later, learners in the teaching group, as did those in the retrieval practice group, outperformed learners in the TnRP and control groups. Retrieval practice possibly causes the learning benefits of teaching.